РОЗМІРИ РЕБРОПЛАВА ПЛЕВРОБРАХІЇ В ЧОРНОМУ МОРІ ВІДПОВІДАЮТЬ ТАКИМ ВИДУ PLEUROBRACHIA PILEUS (O. F. MÜLLER, 1776) - Заїка, В. Є. (Marine Ecological Journal, 2023)
It has been shown that a mistake in determination of the definitive sizes of ctenophore Pleurobrachia, inhabiting the Black sea led to a wrong name of species in “Guide of the fauna…” (1968).